Sustainable surface water dissolved oxygen monitoring at lake 7/1F, Shah Alam, Selangor / Norashikin M. Thamrin … [et al.] - M. Thamrin, Norashikin; Megat Ali, Megat Syahirul Amin; Misnan, Mohamad Farid; Nik Ibrahim, Nik Norliyana; Shaghaghi, Navid (Universiti Teknologi MARA, 2021)
Shah Alam is in Selangor, Malaysia and symbolized with several lakes that are popular among local communities and visitors for leisure and recreational activities. Among of these lakes, few lakes need management to look after its hygienic and well-being to serve its purpose as the recreational lake for the nearby community, such as Lake 7/1F, Shah Alam, Selangor. The secluded location of this water reservoir has made it unpopular, and improper management of it could invite an imbalance environment to its surrounding. Therefore, to initiate the effort, an Internet-of-Thing (IoT) water monitoring system is deployed at this lake to study the dissolved oxygen (DO) level in the water that could indicate the health status of this lake. The system consists of a DO sensor, embedded controller, self-charging power supply, wireless data transmission, and IoT dashboard for in-situ DO measurement. From the analysis, the lake has the normal cycle of DO production, but a dangerous condition is detected when the concentrated DO in the lake water is mostly below the saturation value.